Is dipyridamole useful in improving left ventricular systolic and diastolic function in patients with coronary slow flow?. Issue 10 (25th June 2016) - Suner, Arif; Cetin, Mustafa
Abstract : Background: Coronary slow flow (CSF) is an angiographic finding characterized by delayed opacification of epicardial coronary arteries without obstructive coronary disease. Previous studies have shown greater impairment of left ventricular (LV) systolic and diastolic function in patients with CSF. We aimed to examine the effect of dipyridamole on these functions. Methods: Our study included 40 patients with CSF and 40 subjects with normal coronary arteries. Conventional echocardiography Doppler imaging (CDI) and tissue Doppler echocardiography imaging (TDI) were used to evaluate LV systolic and diastolic function before and 2 months after treatment with dipyridamole. Results: Using CDI, we observed that early diastolic velocity (E) was significantly lower in patients with CSF, while late diastolic velocity (A), E/A ratio, isovolumic relaxation time, and myocardial performance index (MPI) were significantly higher in CSF patients compared with controls. Similarly, while early myocardial velocity (Em) was significantly lower, late myocardial velocity (Am), Em/Am ratio, isovolumic relaxation time (IRT), and MPI were significantly higher in CSF patients according to TDI measurements. Although there was no significant improvement in conventional Doppler parameters, there was significant normalization in tissue Doppler parameters after treatment with dipyridamole. Conclusion: Left ventricular systolic and diastolic function may be negatively affected by CSF. Dipyridamole may improve these functions, especially at the tissue level.